ANALISIS FAKTOR-FAKTOR STRES KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KELURAHAN SERUA TANGERANG SELATAN - Ferry Canova; Risza Putri Elburdah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the factors of work stress and their impact on employee performance at the Serua Sub-District Office, South Tangerang. This research employs a qualitative approach with a descriptive method. Data were collected through in-depth interviews, field observations, and documentation involving employees selected through purposive sampling. Data validity was ensured using source and technique triangulation. The findings indicate that work stress is influenced by three main factors: environmental, organizational, and individual factors. Environmental factors relate to a crowded work environment and high public service demands. Organizational factors include uneven workload distribution, tight deadlines, and ineffective internal communication. Individual factors are associated with differences in adaptability and personal responsibility pressure. Work stress affects employee performance, particularly in terms of work quality, timeliness, and concentration. However, employees continue to demonstrate responsibility in performing their duties and providing public services in accordance with established standard operating procedures. Therefore, systematic work stress management is necessary to improve employee performance and enhance the quality of public services